Pop-culture pedagogy in the music classroom : teaching tools from American idol to YouTube - Biamonte, Nicole (Scarecrow Press, 2011)
Teachers the world over are discovering the importance and benefits of incorporating popular culture into the music classroom. The cultural prevalence and the students' familiarity with recorded music, videos, games, and other increasingly accessible multimedia materials help enliven course content and foster interactive learning and participation. Pop-Culture Pedagogy in the Music Classroom: Teaching Tools from American Idol to YouTube provides ideas and techniques for teaching music classes using elements of popular culture that resonate with students' everyday lives. From popular songs and genres to covers, mixes, and mashups; from video games such as Dance Dance Revolution and Guitar Hero to television shows like American Idol, this exciting collection offers pedagogical models for incorporating pop culture and its associated technologies into a wide variety of music courses. Nicole Biamonte has collected essays that consider a variety of applications. The first Section addresses such general tools as sound mixing, iPods, and YouTube, as well as technology that can be incorporated into almost any music class. The next Section uses pop culture to demonstrate music-theory topics and develop ear-training and rhythmic skills. The final Section examines the musical, lyrical, or visual content in popular songs, genres, or videos to address broader issues and contexts. Although written with college and secondary-school teachers in mind, the methods and materials presented here can be adapted to any educational level [Publisher description].